The bidirectional association of C-peptide with cardiovascular risk in nondiabetic adults and patients with newly diagnosed type 2 diabetes mellitus: a retrospective cohort study - Yan, Shuang-Tong; Sun, Jing; Gu, Zhao-Yan; Miao, Xin-Yu; Ma, Li-Chao; Sun, Ban-Ruo; Fu, Xiao-Min; Liu, Hong-Zhou; Yang, Guang; Fang, Fu-Sheng; Li, Hong (Cardiovascular diabetology, 2022)
Background Recent literature reported the biological role of C-peptide, but this role is still controversial and unclear. The primary aim of this study was to investigate associations between C-peptide and cardiovascular biomarkers as well as events. Methods A total of 55636 participants who had a health examination from 2017 to 2021 were included. Of them, 6727 participants visited the hospital at least twice. Cardiovascular biomarkers like high-sensitivity C-reactive protein (hs-CRP) and high-sensitivity cardiac troponin T (hs-cTnT) were measured and their relationships with fasting C-peptide were evaluated for all participants. Cardiovascular events were obtained during the last visit and their associations with C-peptide were evaluated for those participants who visited the hospital at least twice. Results Among the included participants, 11.1% had a previous type 2 diabetes mellitus (T2DM). In the participants without previous T2DM, the relationships between fasting C-peptide and hs-CRP and hs-cTnT were negative if the value of fasting C-peptide was < 1.4 ng/mL and positive if the value was ≥ 1.4 ng/mL. These relationships remained significant after adjusting for hemoglobin A1c, insulin resistance index, and its interaction with C-peptide, even if the participants were stratified by glucose metabolism status or levels of insulin resistance index. Hazard ratios of cardiovascular events were first decreased and then increased with the increasing of baseline C-peptide levels, though these associations became unsignificant using the multivariate Cox regression model. Unlike the participants without previous T2DM, the associations of C-peptide with cardiovascular biomarkers and events were not significant in the patients with previous T2DM. Conclusions The associations of C-peptide with cardiovascular biomarkers and events were different between the participants without previous T2DM and those with previous T2DM. The effect of C-peptide on cardiovascular risk may be bidirectional, play a benefit role at a low level, and play a harmful role at a high level in the nondiabetic adults and the patients with newly diagnosed T2DM.